THE MINERAL ISOTOPE COMPOSITION OF TWO PRECAMBRIAN CARBONATITE COMPLEXES FROM THE KOLA ALKALINE PROVINCE - ALTERATION VERSUS PRIMARY MAGMATIC SIGNATURES - Tichomirowa M.; Grosche G.; Götze J.; Belyatsky B.V.; Savva E.V.; Keller J.; Todt W. (My University, 2006)
We investigated the isotope composition (O, C, Sr, Nd, Pb) in mineral separates of the two Precambrian carbonatite complexes Tiksheozero (1.98 Ga) and Siilinjärvi (2.61 Ga) from the Karelian-Kola region in order to obtain information on Precambrian mantle heterogeneity. All isotope systems yield a large range of variations. The combination of cathodoluminescence imaging with stable and radiogenic isotopes on the same samples and mineral separates indicates various processes that caused shifts in isotope systems. Primary isotope signatures are preserved in most calcites (O, C, Sr, Pb), apatites (O, Sr, Nd), amphiboles (O), magnetites (O), and whole rocks (Sr, Nd). The primary igneous C and O isotope composition is different for both complexes (Tiksheozero: δ13C = - 5.0‰, δ18O = 6.9‰; Siilinjärvi: δ13C = - 3.7‰, δ18O = 7.4‰) but very uniform and requires homogenization of both carbon and oxygen in the carbonatite melt. The lowest Sr isotope ratios of our carbonates and apatites from the Archaean Siilinjärvi (0.70137) and the Palaeoproterozoic Tiksheozero (0.70228) complexes are in the range of bulk silicate earth (BSE). Positive εNd values of the two carbonatites point to very early Archaean enrichment of Sm/Nd in the Fennoscandian mantle. No HIMU components could be detected in the two complexes, whereas Tiksheozero carbonatites give the first indication of Palaeoproterozoic U depletion for Fennoscandia. Sub-solidus exchange processes with water during emplacement and cooling of carbonatites caused an increase in the oxygen isotope composition of some carbonates and probably also an increase of their 87Sr/86Sr ratio. A larger increase of initial Sr isotope ratios was found in carbonatized silicic rocks compared to carbonatite bodies. The Svecofennian metamorphic overprint (1.9-1.7 Ga) caused reset of Rb/Sr (mainly mica) and Pb/Pb (mainly apatite) isochron systems. © 2006 Elsevier B.V. All rights reserved.
Keywords: C-O-SR-ND-PB ISOTOPES; CARBONATITE; KOLA ALKALINE PROVINCE; MANTLE HETEROGENEITY; MANTLE SOURCE; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой